Systematic Literature Review: Analysis Of Financial Distress in Manufacturing Companies on The Indonesia Stock Exchange Using The Altman Z-Score Method - Nabila, Zahara; Ariyani, Reni; Olifia, Norma; Uyun, Qurotul; Rahmatika, Dien Noviani (EAJ (Economic and Accounting Journal), 2026)
This study aims to synthesize scientific evidence through the Systematic Literature Review (SLR) method to map and analyze financial distress predictions in manufacturing companies listed on the Indonesia Stock Exchange (IDX) with a focus on the application of the Altman Z-Score Model. Given the strategic role of the manufacturing sector in the national economy, early detection of bankruptcy risk is crucial. This study uses the PRISMA protocol by analyzing 30 accredited journal articles published in the period 2020–2025, with the inclusion criteria of IDX manufacturing companies that apply the Altman Z-Score. The synthesis results show that the level of financial distress in IDX manufacturing companies fluctuates between sub-sectors and is influenced by time dynamics, especially during the pandemic. Most studies indicate that many companies are in the gray area, reflecting moderate financial vulnerability. In general, the Altman Z-Score shows a high level of prediction accuracy (above 70%), although in certain sub-sectors alternative models such as Zmijewski and Springate are considered superior. In addition, components X3 (EBIT/Total Assets) and X2 (Retained Earnings/Total Assets) are consistently the most dominant variables in determining financial distress. The conclusion of this SLR confirms that the Altman Z-Score remains relevant and reliable as a bankruptcy prediction tool for BEI manufacturing companies. These findings contribute theoretically to mapping the latest research developments and provide practical implications for investors, creditors, and management in decision-making and financial risk mitigation.